2019
DOI: 10.5194/ica-proc-2-61-2019
|View full text |Cite
|
Sign up to set email alerts
|

Enriching complex road intersections from OSM with traffic-related behavioral information

Abstract: <p><strong>Abstract.</strong> Bicycle traffic in urban environments has various complex aspects in relation to the used space and the assigned transport infrastructures, especially in urban environments. Depending on the traffic situations, the built static urban infrastructure design, and, the other traffic participants involved, there are more or less challenging possibilities of its representation. Modelling and simulating urban bicycle traffic should include the interactions to other traf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…As stated in previous research [1], we already identified numerous insights from a case study at a small roundabout in Germering, Germany, which is pictured in Figure 1. There are complex interaction and communication patterns between the 3 types of vehicle drivers, bicyclists and pedestrians which are directly dependent on the infrastructural design and the changing visibilities of every road user.…”
Section: Traffic Observation and Documentation Of Maneuvers And Gesturesmentioning
confidence: 55%
See 2 more Smart Citations
“…As stated in previous research [1], we already identified numerous insights from a case study at a small roundabout in Germering, Germany, which is pictured in Figure 1. There are complex interaction and communication patterns between the 3 types of vehicle drivers, bicyclists and pedestrians which are directly dependent on the infrastructural design and the changing visibilities of every road user.…”
Section: Traffic Observation and Documentation Of Maneuvers And Gesturesmentioning
confidence: 55%
“…In our approach, we first define flows for a traffic simulation network that can optionally be a depiction of real-world infrastructure [30] and base on real-world observations at traffic counts or extracted information from video data acquisitions. With the collected data, we can then classify observed maneuvers based on specifying their appearances and trajectory shapes together with variations in speed and their frequencies within the observation period [1]. With these collections, it is possible to design scenarios for bicycle simulator studies [2].…”
Section: Methodological Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach makes use of the netconvert tool [2] of the microscopic traffic flow simulation environment SUMO [3]. Similar to the approach of Keler, Grigoropoulos, and Mussack (2019) [4], we start with an extraction of raw OSM data by selecting a rectangle investigation area. After the conversion step into a PlainXML format, we are able to improve manually the quality of the road network representation by adjusting elements and specific details of the transportation infrastructure via the tool netedit (of SUMO).…”
Section: Open Geodata Extraction and Conversion Into Simulation Networkmentioning
confidence: 99%
“…The DYNA4 approach is addressed in Keler et al (2018), Keler et al (2019aKeler et al ( , 2019b and in Malcolm (2019). Similar to the workflow in Figure 3, most map designs rely on real investigation areas or extracts of these from OSM (Keler et al 2021).…”
Section: The Dyna4 Approachmentioning
confidence: 99%